Inter-ring band-transfer limited by laser wavelength drift in DD MB-OFDM metro networks - Soeiro, R. O. J. (2017)
The performance of a virtual carrier assisted direct-detection single sideband (SSB) multiband (MB) orthogonal frequency division multiplexing (OFDM) metropolitan network impaired by the inter-ring OFDM band-transfer and laser wavelength drift effects is assessed numerically. A 42.8-Gbit/s three-band and a 57.07-Gbit/s four-band SSB-MB-OFDM signal, both with a band spacing of 6.25 GHz, are considered. In order to assess the system resiliency against the inter-ring band-transfer and laser wavelength drift effects, 16-quadrature-amplitude modulation (QAM) and 32-QAM are employed. It is shown that, considering only the impairments related with the inter-ring band-transfer, i.e., neglecting the laser wavelength drift, and using band-selectors with similar -3 dB bandwidths to realize inter-ring band-transfer, a maximum of 4 and 12 band-transfers are achieved with an optical signal-to-noise ratio (OSNR) penalty not exceeding 1 dB, for 16-QAM and 32-QAM, respectively. When the inter-ring band-transfer and laser wavelength drift effects are considered together, the frequency drift ranges leading to an OSNR penalty not exceeding 1 dB, when one band-transfer is considered, are between -400 and 200 MHz, and between -500 and 500 MHz, for the transferred band, adopting 16-QAM and 32-QAM, respectively. The frequency drift ranges are reduced to between -100 and 100 MHz, and between -200 and 200 MHz for four band-transfers, adopting 16-QAM and 32-QAM, respectively.